1998
DOI: 10.1007/s002210050452
|View full text |Cite
|
Sign up to set email alerts
|

Environmental enrichment alters organizational features of the forepaw representation in the primary somatosensory cortex of adult rats

Abstract: The cortical forepaw area of young adult rats was mapped by recording the response properties of small clusters of neurons in layer IV of the primary somatosensory (SI) cortex. First we quantitatively analyzed the somatotopic organizational features of the cortical forepaw representation in terms of areal extent and topography, receptive field (RF) sensory modality, size, and location. We also assessed the influence of environmental enrichment, known to induce structural alterations in cortical connectivity, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
70
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(79 citation statements)
references
References 49 publications
8
70
0
1
Order By: Relevance
“…A parylene-coated tungsten microelectrode (ϳ1 M⍀ at 1 kHz; World Precision Instruments, Hertfordshire, UK) was moved perpendicular to the cortical surface in Cartesian coordinates by a three-dimensional stepping micromanipulator (Märzhauser; Fine Science Tools, Vancouver, British Columbia, Canada). Using the recording artifact generated by the microelectrode contact with the cortex surface as a zero level, we advanced the electrode to a depth of ϳ650 -700 m to record responses from small clusters of neurons (two to four) in layer IV (Waters et al, 1995;Coq and Xerri, 1998). Sites of electrode penetration were identified relative to the vasculature of the cortical surface.…”
Section: Electrophysiological Mappingmentioning
confidence: 99%
“…A parylene-coated tungsten microelectrode (ϳ1 M⍀ at 1 kHz; World Precision Instruments, Hertfordshire, UK) was moved perpendicular to the cortical surface in Cartesian coordinates by a three-dimensional stepping micromanipulator (Märzhauser; Fine Science Tools, Vancouver, British Columbia, Canada). Using the recording artifact generated by the microelectrode contact with the cortex surface as a zero level, we advanced the electrode to a depth of ϳ650 -700 m to record responses from small clusters of neurons (two to four) in layer IV (Waters et al, 1995;Coq and Xerri, 1998). Sites of electrode penetration were identified relative to the vasculature of the cortical surface.…”
Section: Electrophysiological Mappingmentioning
confidence: 99%
“…Diamond et al, 1964;Diamond et al, 1966;Volkmar and Greenough, 1972). Although not a ubiquitous phenomenon, morphological plasticity following exposure to EC has been demonstrated in several other brain regions that are involved in the processing and/or response to environmental stimuli, including the auditory cortex (Greenough et al, 1973), primary somatosensory cortex (Coq and Xerri, 1998), hippocampus and entorhinal cortex (Fiala et al, 1978;Moser et al, 1997;Rampon et al, 2000), amygdala (Nikolaev et al, 2002), basal ganglia (Comery et al, 1995;Comery et al, 1996) and cerebellar cortex . Initially, alterations in neuronal structure were the focus of investigation, however, more recently it has become clear that other components of the nervous system, such as macroglial cells and cerebrovasculature elements, also exhibit robust plasticity in response to experience.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is substantial evidence to indicate that so matosensory cortices are promising targets for inducing plasticity in these circuits. Decades of primate research have demonstrated the propensity for plasticity in somatosensory cortex that follows experience or practiced behaviour [107,108] cognitive factors of learning and attention [109][110][111][112], lesion of the peripheral or central nervous system [113,114] and direct micro-stimulation in the absence of peripheral stimulation [115]. It is notable that Belci et al [105] observed reductions in cSP and improvements in somatic percepts, effects that may be attributed to direct stimulation of the primary somatosensory cortex.…”
Section: Resultsmentioning
confidence: 99%